Analisis Indeks Pencemaran Airtanah di DKI Jakarta dengan Interpolasi Spasial: Analysis of Groundwater Pollution Index in DKI Jakarta using Spatial Interpolation - Dimas Ardi Prasetya; I Putu Santikayasa; Iqbal Hanun Azizi (Jurnal Teknik Sipil dan Lingkungan, 2021)
Everyone needs water to his life and his activity. Groundwater pollution is one of the problems in Indonesia. The increasing number of the show an increase water needs. They were filled with groundwater needs. There has been decreasing groundwater that is occupied in quantity and quality. The research was done in Jakarta, consisting of 42 sub-district. Research takes into account the condition of the dry season. Uses index research quality of groundwater pollution. Monitoring parameter groundwater consisting of physics, chemical and biology paramater. The research consists of determining the pollution index in Jakarta, analysis of groundwater pollution, and predicted entanglement with an index pollution population density. The research uses spatial interpolation to determine locations. Pollution index calculation used calculation storet. The measurement results in the rate used in the analysis index groundwater pollution. The research results obtained index value has increased pollution are on the north and central of Jakarta. The research results obtained East Jakarta having the condition geology that porous. The value of the groundwater pollution index was in north Jakarta. The results of the study indicated by a map pollution index the quality of groundwater during three periods. Index pollution in Jakarta consisting of pollution until the same as the quality standard. Research shows the absence of correlation with the population with the pollution groundwater quality.